Atmospheric acoustic remote sensing - Bradley, Stuart (CRC Press, 2008)
A guide for using SODARs to perform wind measurements and data analysis for scientific, environmental, or alternative monitoring applications. It explains the underlying science, principles, and operational aspects of acoustic radars. It explores applications in environmental research, boundary layer research, and wind power and loading.